THE SCOPE OF STRESS IN SOCIETY AND PSYCHOSOCIAL CARE CENTER A TREATMENT SITE (Fiep Bulletin - online, 2015)
Objective: Educate the population that there are specific locations of treatment for psychosocial diseases and clarify that stress is considered to be one of those. Methods: It is an observational, prospective study with an epidemiological method of causal and non-causal Association, with qualitative and quantitative approach in which 100 people have agreed to participate in a survey, responding to a form, containing objective questions which were used as variables. The data, once compiled, were presented in tables and graphs of simple frequency expressed in numbers and percentages. Ethical aspects have been respected, in accordance with resolution No. 196/96 (CNS-MS). Results: 50% Women; Men 50%; the majority of respondents 65.16% never heard of CAPS, while the minority 34.84% already heard something about the CAPS; 56.13% of respondents believe that the CAPS have an effective treatment, while 43.87% believe that the treatment of CAPS is not effective; 68.39% of respondents don't know that the CAPS have stress treatment, 31.61% know that the CAPS have stress treatment; most men are less stressed that women who exhibit a high level of stress. Conclusion: The results suggest that most people consider themselves to be stressed, but didn't know it was a psychosocial illness and had treatment offered by the psychosocial care center (CAPS).
Keywords: CAPS; Stress; Psychosocial Illness.